Active Case Finding for Coronavirus Disease 2019 among People in Risk Areas, Mae Sot District, Tak Province - จันทมัตตุการ, จรัญ; เอี่ยมรอด , กิตติพัทธ์ (Journal of Health Science of Thailand, 2022)
During the end of 2020 to January 2021, cases of coronavirus disease 2019 were detected near the Thailand-Myanmar border in Mae Sot district, Tak province which might lead to wider outbreaks in the country. A survey was conducted to determine coronavirus disease 2019 infection among people in risk areas of Mae Sot district. Active case finding was performed in February 2021, and health education, interview and nasopharyngeal swab collection were included. The specimens were examined for SARSCoV-2 by real-time RT-PCR at laboratories that has been accredited for medical testing laboratories. The survey areas were Pacharoen food market, Un Saw Myanmar community, warehouse and factories near the Thailand-Myanmar border, where a lot of Myanmar migrants stayed and there were COVID-19 case reports or suspected outbreak. Frequency, percentage, 95% CI, mean and standard deviation were used to present results of the analysis. A total of 4,296 people 71 (1.7 %,95%CI=1.2-2.1) were positive for SARS-CoV-2. Of 3,208 people in Pacharoen food market, 18 (0.6%, 95%CI=0.3-0.8) were positive for SARS-CoV-2. Of 499 people in Un Saw Myanmar community, 14 (2.8%, 95%CI=1.3- 4.2) were positive. Among 417 people in the warehouse, 39 (9.4%, 95%CI=6.5-12.1) were positive. None of those in the factories was positive for SARS-CoV-2. The coronavirus disease 2019 infection was found in children, adults and the elderly. Both males and females were similarly infected with the virus. When there is a suspected outbreak of coronavirus disease 2019 near the Thailand-Myanmar border, it is useful to perform active case finding in the risk areas. Disease prevention through DMHTT measures should be encouraged among Myanmar migrants and the measures should be strengthened in the crowded community.